Argumentación jurídica, lenguaje y formas de vida - Trujillo, Julián Fernando (2023)
This artic le presents Wittgenstein’s influence on several theories of legal argumentation, such as those advanced by Perelman and Olbrechts, Toulmin, Robert Alexy, and Aulis Aarnio. For Aarnio, Wittgenstein’s concepts of “language games” and “ways of life” have prov ed very significant. As this article will show, his model of argumentation presupposes a communitarian way of life, a certain kind of a political way of life, and a discourse that satisfies some basic standards of rationality.